FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN INDUSTRI MAKANAN DAN MINUMAN YANG TERDAFTAR DIBURSA EFEK INDONESIA - SHELVY ANGELYA; ERIKA JIMENA ARILYN (Jurnal Bisnis dan Akuntansi, 2017)
The purpose of this research is to get empirically evidence the influence of profitabillity, tangibility, non-debt tax shields, growth opportunity, and liquidity toward capital structure. The object of this research is food and beverage industry that listed in Indonesia Stock Exchange for period 2010-2015. The purposive sampling is used as sampling technique, where 13 companies met the criteria and the hypothesis was analyzed using panel data regressions with random effect model. The result of this research shows that profitability, tangibility, and liquidity influence the capital structure while non-debt tax shields and growth opportunity do not influence the capital structure.